Polysomnography‐derived sleep parameters as a determinant of nocturnal blood pressure profile in patients with obstructive sleep apnea - Kuwabara, Mitsuo (J Clin Hypertens (Greenwich), 2018)
Obstructive sleep apnea causes blood pressure (BP) surges during sleep, which may lead to increased sleep‐onset cardiovascular events. The authors recently developed an oxygen‐triggered nocturnal BP monitoring system that initiates BP measurements when oxygen desaturation (SpO(2)) falls below a variable threshold. The association between nocturnal BP parameters obtained by nocturnal BP monitoring and simultaneously examined polysomnography‐derived sleep parameters in 116 patients with obstructive sleep apnea (mean age 57.9 years, 85.3% men) was studied. In multivariable analysis with independent factors of age, body mass index, sex, and polysomnography‐derived measures (apnea‐hypopnea index, apnea index, arousal index, lowest SpO(2), and SpO(2) < 90%), apnea‐hypopnea index (β = .26, P = .02) and lowest SpO(2) (β = −.34, P < .001) were independent determinants of hypoxia‐peak systolic BP (SBP), defined as the maximum SBP value measured by nocturnal BP monitoring. Similarly, apnea‐hypopnea index (β = .21, P = .04) and lowest SpO(2) (β = −.49, P < .001) were independent determinants of nocturnal SBP surge, defined as the difference between the hypoxia‐peak SBP and the average of the SBP values within 30 minutes before and after the hypoxia‐peak SBP, measured by the fixed‐interval function in the manner of conventional ambulatory BP monitoring. In conclusion, in polysomnography‐derived parameters, lowest SpO(2), defined as the minimum SpO(2) value during sleep, is the strongest independent determinant of hypoxia‐peak SBP and nocturnal SBP surge measured by nocturnal BP monitoring. Our findings suggest that the severity of the decrease in SpO(2) and the frequency of such decreases would be important indicators to identify high‐risk patients who are likely to develop cardiovascular events specifically during sleep.